High‐Strength and Injectable Supramolecular Hydrogel Self‐Assembled by Monomeric Nucleoside for Tooth‐Extraction Wound Healing. Issue 13 (14th February 2022) - Wang, Zheng; Zhang, Yanan; Yin, Yijia; Liu, Jiang; Li, Peiran; Zhao, Yuxi; Bai, Ding; Zhao, Hang; Han, Xianglong; Chen, Qianming
Abstract: Hydrogels with high mechanical strength and injectability have attracted extensive attention in biomedical and tissue engineering. However, endowing a hydrogel with both properties is challenging because they are generally inversely related. In this work, by constructing a multi‐hydrogen‐bonding system, a high‐strength and injectable supramolecular hydrogel is successfully fabricated. It is constructed by the self‐assembly of a monomeric nucleoside molecular gelator (2‐amino‐2′‐fluoro‐2′‐deoxyadenosine (2‐FA)) with distilled water/phosphate buffered saline as solvent. Its storage modulus reaches 1 MPa at a concentration of 5.0 wt%, which is the strongest supramolecular hydrogel comprising an ultralow‐molecular‐weight (MW < 300) gelator. Furthermore, it exhibits excellent shear‐thinning injectability, and completes the sol–gel transition in seconds after injection at 37 °C. The multi‐hydrogen‐bonding system is essentially based on the synergistic interactions between the double NH2 groups, water molecules, and 2′‐F atoms. Furthermore, the 2‐FA hydrogel exhibits excellent biocompatibility and antibacterial activity. When applied to rat molar extraction sockets, compared to natural healing and the commercial hemorrhage agent gelatin sponge, the 2‐FA hydrogel exhibits faster degradation and induces less osteoclastic activity and inflammatory infiltration, resulting in more complete bone healing. In summary, this study provides ideas for proposing a multifunctional, high‐strength, and injectable supramolecular hydrogel for various biomedical engineering applications. Abstract : Simultaneously achieving high strength and injectability in one hydrogel is challenging. A high strength and injectable supramolecular hydrogel is constructed by the self‐assembly of a monomeric nucleoside molecular gelator (2‐amino‐2′‐fluoro‐2′‐deoxyadenosine (2‐FA)). Notably, it exhibits excellent biocompatibility, fast biodegradation, antibacterial property, and osteoclast inhibition, making it a potential candidate biomaterial for tooth‐extraction wound healing and tissue engineering.